(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This study examines the issues of effective management of food industry enterprises in the country in the context of integration with agriculture. The impact of geopolitical instability, resource shortages, and logistics disruptions on food security is analyzed. The interrelation between the volume and quality of agricultural raw materials, their level of processing, and the development of the food industry is also substantiated. The research highlights the importance of strengthening agro-industrial integration, implementing a cluster approach, and utilizing public-private partnership mechanisms.